Development Of Programmable Home Security Using GSM System For Early Prevention - Jamil Alsayaydeh, Jamil Abedalrahim; Ahmad Idil, Abdul Rahman; Baharudin, Zikri Abadi; Wong, Adam Yoon Khang; Aziz, Azwan; Syed Salim, Syed Najib; Zainon, Maslan; Abbasi, Muhammad Inam (Asian Research Publishing Network (ARPN), 2021)
Lately, the security technology business has been offering an inflexible and expensive alert system. Home security assumes an essential role in the current lifestyle to help identify illegal activities. In addition to the increasing familiarity with productive home security system, the execution of real-time alert system is enticing for users. Home security and control of it are among the basic reserves of humanity since the early days. Provided that it is updated with the rapidly changing technology to ensure vast coverage, remote control, reliability, and real time operation. Deploying wireless. technologies for the security and control of home automation systems provides attractive advantages along with an easy-touse interface. In the proposed project, a programmable home security system by using GSM system was developed. Raspberry Pi 3 was used as the main controller (server). A Passive Infrared (PIR) sensor was utilized to detect the intruder when an intrusion occurs. It performs its ability by measuring changes in the infrared rays in its field of view. When any potential break-ins are identified, the pi camera module installed on the Raspberry Pi 3 will capture the intruders' photo. Meanwhile, the installed GSM module will send a warning message to the user, which shall also include the intruders' photo link. Finally, the image will be loaded into the created web page. Along these lines, the user can confirm the message received and take a quick step by reporting the incident to the authorized entity. With everything in mind, this improvement provides a reasonable and easy-to-use home security system